Procedings of the British Machine Vision Conference 2015 2015
DOI: 10.5244/c.29.60
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Image-trained CNN Architectures for Unconstrained Video Classification

Abstract: In this paper, we propose an efficient approach to exploit off-the-shelf image-trained CNN architectures for video classification and evaluate on the challenging TRECVID MED'14 dataset and UCF-101 dataset. Our work is closely related to other research efforts towards the efficient use of CNN for video classification. While it is now clear that CNN-based approaches outperform most state-of-the-art handcrafted features for image classification, it is not yet obvious that this holds true for video classification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 31 publications
(52 reference statements)
3
102
0
Order By: Relevance
“…Considering deep learning methods, our method performs on par and is only outperformed from [33]. [33] makes use of the very deep VGGnet [24], which is a more competitive network than that the Alexnet architecture we rely on. Hence a direct comparison is not possible.…”
Section: State-of-the-art Comparisonsmentioning
confidence: 99%
“…Considering deep learning methods, our method performs on par and is only outperformed from [33]. [33] makes use of the very deep VGGnet [24], which is a more competitive network than that the Alexnet architecture we rely on. Hence a direct comparison is not possible.…”
Section: State-of-the-art Comparisonsmentioning
confidence: 99%
“…video classification in noisy video streams). Nevertheless, we examined the following papers : [15], [16], [17] which presents results of video classification using UCF-101 dataset. The best systems presented in those papers are based on various architectures of Convolutional Neural Networks (CNNs) and achieve accuracy of 80% and more.…”
Section: Experiments and The Discussionmentioning
confidence: 99%
“…Zhongwen Xu et al [19] proposed discriminative CNN video representation to perform event detection from video dataset. Andrej Karpathy et al [6], Joe Yue-Hei Ng [8] and Shengxin Zha [20] used CNN architectures to perform video classification. They also retrained the top layers of their systems to study the generalization performance of their models and reported performance improvements from 88.6 percent to 88.0 percent.…”
Section: Related Workmentioning
confidence: 99%